2013
DOI: 10.5141/ecoenv.2013.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial activity and total phenolic content of three Pinus species

Abstract: This study compared the antimicrobial activity and total phenolic content of three Pinus plants (Pinus densiflora, P. thunbergii, P. rigida) for the first time. The antimicrobial activity of the water fraction of methanol extract of fresh leaves was stronger than that of fallen leaves at any concentrations. The water fraction of crude methanol extract from fresh leaves of P. thunbergii showed a higher growth inhibitory activity against gram-positive and gram-negative bacteria than that of P. densiflora and P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…The antibacterial activity of the Cyclo and Dcm extracts can also be attributed to some phenolic compounds such as pinosylvin monomethyl ether present in these extracts (Table 2). Kim et al 8 showed a good antibacterial activity of pinosylvin monomethyl ether against both Gram positive and Gram negative foodborne bacteria (MIC = 200 μg/mL). Moghrovyan et al 24 tested the antibacterial activity of the ethanolic extract of O vulgare L. against E coli VKPM M‐17, E coli DH5α‐pUC1, S aureus WDCM 5233, and Salmonella enterica .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial activity of the Cyclo and Dcm extracts can also be attributed to some phenolic compounds such as pinosylvin monomethyl ether present in these extracts (Table 2). Kim et al 8 showed a good antibacterial activity of pinosylvin monomethyl ether against both Gram positive and Gram negative foodborne bacteria (MIC = 200 μg/mL). Moghrovyan et al 24 tested the antibacterial activity of the ethanolic extract of O vulgare L. against E coli VKPM M‐17, E coli DH5α‐pUC1, S aureus WDCM 5233, and Salmonella enterica .…”
Section: Resultsmentioning
confidence: 99%
“…Dried oregano is used as a medication for gastrointestinal troubles, antitussive, expectorant, 7 as well as in food preparations, liquor production, and as a pesticide 2 . Today, there is a huge consumer's demand for foods that are minimally processed and free from synthetic chemical preservatives 8 …”
Section: Introductionmentioning
confidence: 99%
“…Several hypotheses can be raised to explain the activities of the pine sawdust 175 °C extract. Numerous studies have shown positive relations between antifungal efficiency of natural extracts, contents in total phenolics and antioxidant potential, i.e., free radical scavenging capacity [ 33 , 34 ]. In addition, several authors have suggested that the efficiency of phenolic acids in reducing TCTB production could be linked to their antioxidant properties [ 7 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%